2016
DOI: 10.1007/s11746-016-2914-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonocrystallization of Interesterified Fats with 20 and 30% C16:0 at sn‐2 Position

Abstract: The objective of this study was to induce crystallization in enzymatically interesterified fats (IE) with 20 and 30% palmitic acid at the sn‐2 position using high intensity ultrasound (HIU). The physical blends (PB) used to prepare these two IE were consisted of tripalmitin and high oleic sunflower oil and contained 13.2 and 27.1% tripalmitin, respectively. Crystallization behavior of IE was compared with PB at supercoolings of 9, 6 and 3 °C. Results show that the melting point, SFC, and crystallization rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…This behavior might be related to the MG crystallization process, which occurred slower at 0.1 °C/min compared to the samples that were cooled at 10 °C/min. Previous studies have demonstrated that an induction in the crystallization of lipids takes place when the driving force increases, and this increment can be achieved either through higher supersaturation or supercooling levels (Kadamne et al., , ; Lee et al., ). These studies have also shown that HIU is not effective at inducing crystallization if the content of saturated fatty acids is too low (lower degree of supersaturation), corroborating the lack of effect of HIU on hardness for low MG concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior might be related to the MG crystallization process, which occurred slower at 0.1 °C/min compared to the samples that were cooled at 10 °C/min. Previous studies have demonstrated that an induction in the crystallization of lipids takes place when the driving force increases, and this increment can be achieved either through higher supersaturation or supercooling levels (Kadamne et al., , ; Lee et al., ). These studies have also shown that HIU is not effective at inducing crystallization if the content of saturated fatty acids is too low (lower degree of supersaturation), corroborating the lack of effect of HIU on hardness for low MG concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Oscillatory tests were performed at 25°C by a strain sweep procedure from 8.0 × 10 −4 to 10% at a constant frequency of 1 Hz (6.28 rad/s). The experiments were carried out using a parallel plate geometry (40 mm diameter, 1000 µm gap) (Kadamne, Ifeduba, Akoh, & Martini, 2017a).…”
Section: Oscillatory Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…The G 0 and G 00 values were measured at 25 C using the strain-sweep oscillation procedure by varying the strain% from 8.0 × 10 −4 to 10% at a constant 1 Hz frequency. The Rheology Advantage software was used for data analysis (Kadamne, Ifeduba, Akoh, & Martini, 2017).…”
Section: Oscillatory Rheologymentioning
confidence: 99%
“…Applying shear also has a significant effect on fat crystallization through various manners, such as accelerating fat nucleation, growth, and polymorphic transition, and inducing orientation of fat crystal networks (Tran & Rousseau, 2016). Furthermore, other processing techniques including high-intensity ultrasound (Kadamne, Ifeduba, Akoh, & Martini, 2017;Povey, 2017;Wagh, Birkin, & Martini, 2016) and high pressure processing (Zulkurnain, Maleky, & Balasubramaniam, 2016) have also been found to affect fat crystallization behavior and physical properties, but further research is still needed before these novel methods can be applied in an industrial setting. The crystallization behavior of SLs may also be altered by adding minor components.…”
Section: Crystallization and Melting Behaviormentioning
confidence: 99%